Toward understanding conflicts between customers and employees’ perceptions and expectations: Evidence of Iranian bank - Rostamy, Ali Asghar Anvary (Journal of Business Economics and Management, 2009)
This paper aims to determine influence factors affecting bank service quality, calculate the relative importance of factors from viewpoints of bank customers and employees, and examine the gaps in customers and employees’ perceptions and expectations of the quality of bank services. Accordingly, an empirical investigation was conducted in one of Iranian leading banks (Bank‐e‐Refah). For data collection, an adjusted SERVQUAL questionnaire was developed and distributed among 385 customers and 305 employees. The results show significant difference between customers and employees viewpoints. Understanding the gaps helped bank managers to develop more effective customer‐oriented service plans and employees’ training and development programs.First Publish Online: 14 Oct 2010